Association Between Anti–Citrullinated Fibrinogen Antibodies and Coronary Artery Disease in Rheumatoid Arthritis. Issue 7 (19th May 2018) - Hejblum, Boris P.; Cui, Jing; Lahey, Lauren J.; Cagan, Andrew; Sparks, Jeffrey A.; Sokolove, Jeremy; Cai, Tianxi; Liao, Katherine P.
Abstract : Objective: Antibodies against citrullinated fibrinogen (anti–Cit‐fibrinogen) have been implicated in rheumatoid arthritis (RA) and associated with cardiovascular risk in RA. The objective of this study was to examine the association between anti–Cit‐fibrinogens and coronary artery disease (CAD) outcomes. Methods: We performed the study in an RA cohort based in a large academic institution linked with electronic medical record data containing information on CAD outcomes from medical record review. Using a published bead‐based assay method, we measured 10 types of anti–Cit‐fibrinogens. We applied a score test to determine the association between the anti–Cit‐fibrinogens as a group with CAD outcomes. Principal components analysis (PCA) was performed to assess whether the anti–Cit‐fibrinogens clustered into groups. Each group was then additionally tested for association with CAD. Sensitivity analyses were also performed using a published International Classification of Disease, Ninth Revision code group for ischemic heart disease (IHD) as the outcome. Results: We studied 1, 006 RA subjects (mean ± SD age 61.0 ± 13.0 years; 72.2% anti–cyclic citrullinated peptide positive). As a group, anti–Cit‐fibrinogen was associated with CAD ( P = 1.1 × 10 −4 ). From the PCA analysis, we observed 3 main groups, of which only 1 group, containing 7 of the 10 anti–Cit‐fibrinogens, was significantly associated with CAD outcomes ( P = 0.015). In the sensitivity analysis, all anti–Cit‐fibrinogens as a group remained significantly associated with IHD ( P = 2.9 × 10 −4 ). Conclusion: Anti–Cit‐fibrinogen antibodies as a group were associated with CAD outcomes in our RA cohort, with the strongest signal for association arising from a subset of the autoantibodies.